Pengaruh Medan Magnet Terhadap Efisiensi Bahan Bakar dan Unjuk Kerja Mesin - Prasetyo, Janu; Rubiono, Gatut; Bunawi, Bunawi (Virtual of Mechanical Engineering Article, 2017)
Automotive technology development increase society need for transportation. It increase the demand of fossil fuel. This research is aimed to get the effect of magnetic field due to fuel consumption and engine performance. The experiment is done with Suzuki Smash 110 cc engine. Magnetic field is vary by electric current input as 1,2; 0,8 and 0,6 Ampere. The engine is running at 1750, 2000, 2250 and 2500 rpm. The result shows that the magnetic field has effect due to fuel consumption and engine performance. Magnetic field has lower fuel consumption and more thermal efficiency.